Virtue and the Good Life in the Early Confucian Tradition. Issue 1 (8th February 2018) - Back, Youngsun
Abstract: This essay examines the role of virtue and the status of non‐moral goods in conceptions of the good human life through an exploration of the thought of Confucius and Mencius. Both Confucius and Mencius lived in quite similar worlds, but their conceptualizations of the world differed from each another. This difference led them to hold different views on the role of virtue and the status of non‐moral goods. On the one hand, Confucius highlighted the self‐sufficiency of virtue, but he acknowledged and appreciated the intrinsic and instrumental value of non‐moral goods. On the other hand, while Mencius underscored the role of virtue as the best means to the best ends, he tried to depreciate the value of non‐moral goods. As a consequence, even though their conceptions of the good life were essentially predicated on virtue, they parted company concerning the status of non‐moral goods in human life.